The Phenomenon of Kitchen makatka – Embroidered Cloth - Dąbrowicz, Anna (In the Kitchen. Cultural Sketches on Space, 2019)
Makatka, an ordinary piece of linen with an embroidered straight contour drawing, often with a sentence or an inscription. Who among us has not met at least once with this, generally considered to be kitschy, subject? Fashion for tapestries lasted from the mid-nineteenth century until the 1980s of the last century. After many years of oblivion, makatka again enjoys popularity. In the article I try to answer the questions about the phenomenon of makatka. I discuss the genesis of the makatka, its former and contemporary functions and the meanings that were attributed to it.